(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
This article discusses ways to improve the efficiency of economic activity and the role and importance of innovative development in this process. Improving efficiency creates opportunities to achieve high results through optimal use of resources and accelerates economic development. The article examines technological innovations, resource-efficient management, effective organization of labor resources, improvements in logistics and transportation processes, financial resource management, and the significance of personnel policies. Each of these approaches plays an important role in enhancing economic efficiency and forms the foundation for effective development for countries and businesses. The article explains both the practical and theoretical aspects of improving economic efficiency and proposes strategies that are crucial for ensuring economic stability and competitiveness.